Analisa Teknis Instalasi Kelistrikan Kapal Motor Penumpang Swarna Putri - Razak, Abdul; Firdaus, Firdaus (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2018)
The large consumption of electrical energy is usually influenced by the type of load used. Electrical loads have properties such as, resistive properties, inductive properties and capasitive properties. These properties have an impact on the electrical system that is the power factor. If the power factor is greater (active power) then the electrical system will be better result, otherwise. If the electrical system has low power factor or reactive power which will greatly affect the fuel consumption, so it is needed power factor improvement using capacitor. Electrical System of Passenger Motor Vessel Swarna Putri having a low factor that is equal to 0.619 and this research uses capacitors for power factor improvement. The result shows that the installation of capacitor causes the improvement of power factor to 0,8. The result of the calculation shows that the saving cost for energy per day decreases from Rp10,197,000 to Rp6,104,000Keywords: passenger motor vessel electricity, Power Factors, Electric Energy Consumption